Nematode attack on cowpeas in Nigeria - Caveness, F.E. (1973)
Cowpeas are attacked by 24species of nematodes distributed among 15 general. Fifteen of these 24 species of plant-parasitic nematodes have been founding Nigeria. The most destructive on local cowpea are three species of the root-knot nematode. The root-knot nematodes are also the most wide spreading Nigeria being found abundantly in all states. The reinform nematode has also been proved capable of reducing cowpea yields in Nigeria and is widely distributed. Both kinds of nematode scan cause yield reductions of 20 to 30percent.Thelife cycles of the root-knot nematodes and the reniform nematode have been studied for Nigeria and are essentially the same as reported in the literature for other tropical countries.